A Review of Three-Dimensional Electric Field Sensors - Xiaonan Li; Yu Gu; Zehao Li; Zijian He; Pengfei Yang; Chunrong Peng (Micromachines)
Three-dimensional electric field sensors (3D EFSs) can simultaneously measure electric field components in three mutually orthogonal directions and comprehensively capture the spatial distribution and dynamic changes of the electric field. They can be widely used in atmospheric science, smart grids, aerospace, target detection, and other fields. This paper deeply analyzes the latest progress in 3D EFSs, focusing on four major types of sensors: DC field mill, electro-optic effect, capacitive sensing, and microelectromechanical system (MEMS). It elaborates on their working principles, structural design, and decoupling calibration methods. At the same time, the advantages and disadvantages of various types of 3D EFSs and their applications in different fields are analyzed. Finally, the challenges faced by 3D EFS technology and its future development direction are discussed.